ANALISIS PERTIMBANGAN HAKIM TERHADAP PENJATUHAN PIDANA BAGI PENYALAHGUNA NARKOTIKA GOLONGAN I (Studi Putusan Nomor 86/Pid.Sus/2022/PN.Gdt): English - Dimas Didi Darmawan (Faculty of Law, Universitas Lampung, 2023)
The younger generation is being targeted as the threat of drug seizures rises in Indonesia. Narcotics are substances or drugs that can alter consciousness, cause loss of feeling, lessen or eliminate pain, and cause dependence. They can be derived from plants or non-plant sources and synthetic or semi-synthetic. As a result, drug users who commit crimes need rehabilitation in order to overcome their drug use. For those who commit drug crimes, rehabilitation is a form of punishment with the objective of healing or treatment. However, in practice, judges frequently favor to sentence drug offenders to prison terms and fines, even though offenders can also be sent to rehabilitation. This empirical normative legal study uses primary and secondary data as its data sources and fieldwork and library research as its data collection methods. According to the study's findings, the judge's factors in establishing that the defendant's actions met the requirements of Article 127, paragraph 1, letter an of Law Number 35 of 2009 Concerning Narcotics were taken into consideration in proving the defendant's actions (Narcotics Law). One example is the decision in the drug crime case at the Special Class II Gedong Tataan District Court, which is based on the accuracy of the evidence and the legal facts presented during the trial and the fulfillment of the elements of each of these crimes. It was argued that it was appropriate for the defendants to receive prison sentences and fines rather than engage in medical or social rehabilitation because their status as drug addicts or abuse victims had not been established.